Polyphenol-Rich Larix decidua Bark Extract with Antimicrobial Activity against Respiratory-Tract Pathogens: A Novel Bioactive Ingredient with Potential Pharmaceutical and Nutraceutical Applications - Marta Faggian; Giulia Bernabè; Sara Ferrari; Stefano Francescato; Gianni Baratto; Ignazio Castagliuolo; Stefano Dall'Acqua; Gregorio Peron (MDPI AG, 2021)
Larch (Larix decidua) bark is a sawmill waste, traditionally used for antiseptic, expectorant and dermatological (wound healing, eczema, psoriasis) purposes. In this work, we developed a food-grade dry larch bark extract (LBE) from sawmill by-products using hydro-alcoholic extraction. The antibacterial activity of LBE was evaluated against respiratory-tract pathogens, i.e., Staphylococcus aureus, Streptococcus pyogenes, Streptococcus pneumoniae, Klebsiella pneumoniae, Pseudomonas aeruginosa and Haemophilus influenza, and it was compared to that of grapefruit seed extract (GSE), a commercially available raw material commonly proposed as antibacterial ingredient for over-the-counter products. Procyanidins (PACs) and other polyphenols contents in LBE were determined by HPLC-FLD-MS and HPLC-DAD-MSn, respectively. The antimicrobial activity of LBE and GSE was assessed using the micro-plate dilution technique in concentration range of 2-200 µg/mL, and the safety of these dosages was assessed in cellular and animal models. LBE showed considerable contents of PACs (15% w/w; especially B-type) and other polyphenols (3.8% w/w), among which the characteristic spiropolyphenols larixinol and epilarixinol were identified, together with the flavonoids isoquercitrin and rutin, already reported as growth inhibitors of different respiratory-tract pathogens. LBE showed higher antimicrobial activity compared to GSE, demonstrated by a growth inhibition range of 10-40% towards five of six strains tested, compared to 10-15% of GSE. These results suggest that LBE may represent a natural and sustainable source of active compounds with antibacterial activity for pharmaceutical and nutraceutical applications.